Alterações na qualidade de raízes de mandioca(Manihot esculenta Crantz) minimamente processadas - Alves, Andreia (2005)
Post harvest of cassava roots has been a great concern in food industries and producers due to the short shelf life and high perishability. Several phenomena have been pointed out as responsible for root deterioration. Among them there are physiological aspects, that lead to losses in initial quality through vascular discoloration of parenchymatous tissue. On the other hand, phenomena from microbial origin, which follow the physiological alterations, are responsible for product decomposition. In this context, this work was aimed at investigating the conservation of cassava roots (Manihot esculenta Crantz) submitted to chlorinated water, and stored using different packings: expanded polystyrene trays covered with PVC, multi-shell packing (polyester Saram-13.5µ/polyethylene-100µ) with and without vacuum and exposed to a cold environment (5 ± 0.5°C). Physico-chemical, microbiological, physiological and sensorial analyses were conducted in this study. Results showed that conservation of cassava roots minimally processed under refrigeration seems to be feasible, resulting in adequate conservation for up to 7 day in trays and 24 days for samples kept sealed and under vacuum.